PENGARUH PUPUK ORGANIK DAN PUPUK NPK TERHADAP pH DAN K-TERSEDIA TANAH SERTA SERAPAN-K, PERTUMBUHAN, DAN HASIL PADI SAWAH (Oryza sativa L ) - Elizabeth Kaya (Universitas Tribhuwana Tunggadewi, 2014)
Potassium absorbed by plants in large enough quantities, sometimes even larger than nitrogen. If the potassium in the soil and irrigation water that comes from not sufficient for growth, the plant will suffer from potassium deficiency and its production will be very low. The availability of K in the soil to be absorbed by plants is impportant to support optimal growth optimal and yield. The research aim to establish the pH and available-K soil, K-uptake and growth as well as the results of paddy (Oryza sativa L) due to the treatment of organic fertilizer and NPK fertilizer. The study was designed using a Randomized block design (RBD) 3 x 5 factorial with 3 replications. The first factor is the organic fertilizer (O) which consists of two levels, ie O0 without organic fertilizer, O1 3 tons ha-1 (6 kg plot-1) straw compost, and O2 3 tons ha-1 (6 kg plot-1) manure. The second factor is the NPK fertilizer (A) which consists of three levels, namely A0 without NPK fertilizer; A1 25% x the recommended dose (75 kg ha-1); A2 50% x the recommended dose (150 kg ha-1); A3 75% x the recommended dose (225 kg ha-1); and A4 100% x the recommended dose (300 kg ha-1). The results showed that combination of the organic fertilizer with NPK fertilizers can increase soil pH, the availability of potassium (K) of paddy soil, uptake of potassium (K), and the number of tillers per hill. Organic fertilizer can increase vegetative growth (plant height) and yield of rice plant ( number of grains per panicle, number of filled grains per panicle and milling dry grain weight yield ), whereas NPK fertilizer can independently increase the plant height. Combination dose of 3 tons of manure ha-1 and 300 kg NPK ha-1 in increasing soil pH by 6.00, straw compost dose combination of 3 tons ha-1 and 300 kg NPK ha-1 can increase K-available soil 35.60 ppm, potassium uptake of rice plants from 1.36 % to 2.20 %, and the number of tillers per hill of 23.10 became 33.13 tillers